TRANSHIATAL ESOPHAGECTOMY WITHOUT THORACOTOMY FOR CARCINOMA OF THE THORACIC ESOPHAGUS - Hakan HALICI; Musa AKOĞLU; Vedat KIRIMLIOĞLU; Onay GÜNEŞ; Haldun GÜNDOĞDU; Özar AKALIN; Orhan ELBİR (Turkish Journal of Gastroenterology, 2020)
-